(untitled) (International Journal of Environmental Sciences, 2025)
In Indonesia, the demand for cosmetics continues to increase, this is what drives more and more cosmetic industries to compete in creating new products with the advantages that each company has. Make Over products are in the top three as the cosmetics most chosen by Indonesian women in 2023. In the process of purchasing decisions, Make Over cosmetic products can be influenced by several factors that influence consumers to make purchasing decisions. The type of research used in this study is explanatory research. The population in this study were all Instagram followers of makeover.id. The sample of respondents in this study was 100 people. Hypothesis testing using the SmartPLS software program version 3. The research results show that Beauty Influencer, Electronic Word Of Mouth have no influence on brand image and Price has an influence on Brand Image. Other results show that Brand Image, Price have no influence on purchase decisions, while Beauty Influencer and Electronic Word of Mouth have an influence on Purchase Decisions. Beauty Influencers have no influence on Purchase Decisions through Brand Image. Electronic Word of Mouth has no influence on Purchase Decisions and Price has no influence on Purchase Decisions through Brand Image.